(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Study on the impact of "Thang thanh giang troc" dry extract on the hematopoietic function of white rats Subject and method: The hematopoiesis function was evaluated Wistar white rats according to Vietnam Health Ministry’s regulations and WHO guidelines on the effectiveness and safety of the medicine. Results: The dry extract " Thang thanh giang trọc" at 0,735 g/kg/24 hours and 2,205 g/kg/24 hours for 90 consecutive days did not effects the red blood cells, hemoglobin content, hematocrit, Mean Corpuscular Volume, platelets and blood white cells; the changes were not statistical significance (p> 0.05) between the research group and control group. Additionally, the macroscopic morphology and microscopic images of rat’s livers and kidneys were within the normal limits. Conclusion: The dry extract "Thang thanh giang troc" does not affect the hematopoietic function of Wistar white rats.